Recriando a educação infantil em tempos de pandemia Covid 19 - Terebinto, Leila Carla (2022)
The goals of this research are to reflect on play and children's cultures in the class in which I work as a teacher, in order to qualify my work proposal in Early Childhood Education. I also seek to understand play, the forms of play in our classroom, as a free, spontaneous, and cultural action, enabling children to interact, participate, make choices, make decisions, and develop their initiative and autonomy. This whole learning process needed to have its methods modified, due to the closing of schools because of the Coronavirus pandemic. As a research problem, we are anxious to find answers to the following questions: Is it possible, through dialogue about the times, spaces, and studies undertaken in the search for possible paths that offer us answers, even if provisional and temporary, to reach the objectives proposed in this research, i.e., to reflect on children's games and cultures in the classes I work as a teacher, in the remote modality? Is it possible, through dialogue about the times, spaces, and studies undertaken in the search for possible paths that offer us answers, even if provisional and temporal, to reach the goals proposed in this research? Finally, this autobiographical research intended to reflect Wallonian reflections on the playful, creative, affective mediation of the teacher - student, looking sensitively at the child as a whole. We realized the importance of the construction of knowledge and culture, through children's sociocultural mediations, which require from the school and from the teachers innovative pedagogical change and reorganization, and that more than ever were tested now, during the pandemic teaching.